2016
DOI: 10.1002/ajpa.22971
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying variation in human scalp hair fiber shape and pigmentation

Abstract: Overall, these results suggest the usefulness of chemical methods for the elucidation of nonperceptible differences in scalp hair color and highlight the need for improvements in our assessment and understanding of hair fiber curvature. Am J Phys Anthropol 160:341-352, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 58 publications
2
39
0
Order By: Relevance
“…Quantitative studies on the type and amount of melanin in hairs relating to the ranges of hair color expression offer an effective avenue to study hair color and composition at a chemical level (Ito & Jimbow, ). Chemical analysis of melanin in hair by High Performance Liquid Chromatography (HPLC; Ito & Wakamatsu, ; Lasisi, Ito, Wakamatsu, & Shaw, ) has revealed a relationship between hair color and the quantity of melanin within hair. The ratio of pheomelanin to eumelanin can be determined chemically, though it may not be visually discernible.…”
Section: Hair Morphology Pigmentation and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative studies on the type and amount of melanin in hairs relating to the ranges of hair color expression offer an effective avenue to study hair color and composition at a chemical level (Ito & Jimbow, ). Chemical analysis of melanin in hair by High Performance Liquid Chromatography (HPLC; Ito & Wakamatsu, ; Lasisi, Ito, Wakamatsu, & Shaw, ) has revealed a relationship between hair color and the quantity of melanin within hair. The ratio of pheomelanin to eumelanin can be determined chemically, though it may not be visually discernible.…”
Section: Hair Morphology Pigmentation and Developmentmentioning
confidence: 99%
“…Diversity in human scalp hair morphology can be attributed to the variation in hair form across a person's scalp, changes that develop over time because of age or health, differences that exist among individuals, and those caused by a person's genetic background. Empirical research quantifying hair characteristics in different populations has long been pursued in anthropology (Banerjee, 1965;Hausman, 1925aHausman, , 1925bHausman, , 1928Hausman, , 1934Hrdy, 1973;Lasisi et al, 2016;Trotter, 1930;Wynkoop, 1929), forensic science (Bisbing & Wolner, 1984;Gaudette, 1978;Gaudette & Keeping, 1974;Strauss, 1983;Wickenheiser & Hepworth, 1990), and continues to be done in cosmetic research (Bernard, 2003;De La Mettrie et al, 2007;Thibaut et al, 2007). A common, up-to-date lexicon that is current and easily transferable among disciplines would facilitate the development of innovative and transdisciplinary methods to analyze hair.…”
Section: Use Of Microscopy In Hair Characterization and Identificationmentioning
confidence: 99%
“…Though the classification is complex, [2,7] certain combinations of these properties tend to be associated with hairs of specific ethnicity [Asian: straight, black, round cross section; European: black-blonde, straight-wavy, slightly elliptical; African: curly, black, strongly elliptical]. [8] Hairs grow from follicles, which extend from the subcutis through dermis and epidermis to the surface of the skin. During its growth, a hair develops its complex morphology on all structural levels.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Fratto & Davis (2011) found that melanistic (black fur) fox squirrels (Sciurus niger) had significantly thinner body hairs and thicker tail hairs than the other fur colours, presumably to offset increased heat absorption due to the darker coloured fur. Human hair also exhibits a wide range of physical characteristics including fibre shape, curvature, kink, and colour (Restano et al 2001, Lasisi et al 2016, De La Mettrie et al 2019. Within humans there is also variation in the cross-sectional shape of hair follicles, both in terms of width and shape (round vs. oval).…”
Section: Introductionmentioning
confidence: 99%
“…Within humans there is also variation in the cross-sectional shape of hair follicles, both in terms of width and shape (round vs. oval). Specifically, Asian populations have thicker crosssectional area (Lasisi et al 2016) and straighter hair (Fujimoto et al 2008), whereas humans of African descent have a more elliptical cross-sectional shape and greater curvature (Lasisi et al 2016). However, given these general differences among the major human groups, De La Mettrie et al (2019) warn that these broad classifications do not adequately represent the full variation in human hair and that eight categories of hair type might represent a better classification scheme.…”
Section: Introductionmentioning
confidence: 99%